2022
DOI: 10.1097/hrp.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Brick by Brick: Building a Transdiagnostic Understanding of Inflammation in Psychiatry

Abstract: Inflammatory phenomena are found in many psychiatric disorders-notably, depression, schizophrenia, and posttraumatic stress disorder. Inflammation has been linked to severity and treatment resistance, and may both contribute to, and result from, the pathophysiology of some psychiatric illnesses. Emerging research suggests that inflammation may contribute to symptom domains of reward, motor processing, and threat reactivity across different psychiatric diagnoses. Reward-processing deficits contribute to motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…Recent studied have shown that in many mental diseases, including schizophrenia, an inflammatory process develops in NAc, and this is associated with abnormal DA concentration in this brain area [ 88 , 89 ]. This can result in neuronal atrophy and changes in the axo-dendritic system, leading to the exacerbation of disease symptoms.…”
Section: Impairment Of the Synaptic Plasticity And Dysregulation Of S...mentioning
confidence: 99%
“…Recent studied have shown that in many mental diseases, including schizophrenia, an inflammatory process develops in NAc, and this is associated with abnormal DA concentration in this brain area [ 88 , 89 ]. This can result in neuronal atrophy and changes in the axo-dendritic system, leading to the exacerbation of disease symptoms.…”
Section: Impairment Of the Synaptic Plasticity And Dysregulation Of S...mentioning
confidence: 99%
“…Something that is fairly odd is that so little attention has been paid to the possible role of cytokines in causing astroglial-induced changes in the function of the DDCS. After all, astrocytes are known to be of great significance in all sorts of processes that cause severe neuroinflammation [61][62][63][64][65], and so why would this not play a role in the lighter forms that are obvious in mental disorders [7,10,21]? Although microglia may be considered the dominant immunocompetent cells of the CNS, astrocytes participate fully in inducing and mediating the neuroinflammatory responses.…”
Section: Astrogliamentioning
confidence: 99%
“…[4] on the influence of grief on the function of B and T cells and hormone levels in the spouses of deceased patients initiated what would later develop into psychoneuroimmunology [5][6][7]. Currently, the connection between the functioning of the immune system and the development of mental disorders is widely accepted [8][9][10][11]. This is especially well conceived for depression [12][13][14][15], schizophrenia [16][17][18] and posttraumatic stress disorder [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory phenomena are considered part of the pathophysiology of both chronic gastrointestinal disorders and chronic psychoses [ 72 , 73 ]. The interplay between gastrointestinal symptoms and mental health disorders has been widely discussed in relation to several disorders [ 72 ].…”
Section: Collaboration With Gastroenterologistsmentioning
confidence: 99%